RANCANG BANGUN SISTEM INFORMASI BIDANG KESISWAAN BERBASIS ANDROID PADA SMKN 8 PADANG - Khairul Afdhal; Elfi Tasrif (Voteteknika (Vocational Teknik Elektronika dan Informatika), 2019)
The Student Field is an important unit for every school in Indonesia, especially for SMKN 8 Padang. The role of student affairs helps schools to deal with various types of violations that students do in the school environment in the teaching and learning process including student absentee management, as well as managing extracurricular activities that interest students. The Student Information System Field of SMKN 8 Padang is based on Android, with this information system users can access anytime and anywhere regarding the rules and regarding extracurricular activities. If students are found committing a violation, they will be directly inputted with the android by the teacher who found the violation committed by the student, and the teacher input the student's attendance. Users who have logged in can enter their own extracurricular interest. All data inputted with Android will be stored on a web server based on Codeigniter framework programming using a MySQL database. The results obtained from the implementation of this student field application are to facilitate the SMK Negeri 8 apparatus, especially in the student field, to record students who commit violations, students who take extracurricular activities and absenteeism that were previously done manually now become digital using mobile phones that can be taken anywhere.Keywords: Information System, Android, Web Programming, CodeIgniter.